The Appropriate Age to Introduce English as a second Language in Libyan Public Schools and its Linguistic and Cultural effect: Teachers' Perspectives (Journal of Academic Research, 2023)
This research paper aims to explore Libyan teachers' perceptions of introducing English language at an early age in Libyan public schools. It touches on some issues related to upon which school stage English is best introduced, what benefits that Libyan students might gain and what impacts teaching English at an early stage might have on student' first language and culture. To deal with these issues, a quantitative tool: a questionnaire was used to collect data. It was distributed to 64 Libyan teachers who were in service at the Department of English in the Faculty of Arts, Misurata University. After analyzing the collected data, the findings revealed that English is better introduced at an early stage in Libyan public schools because this will have positive effects on their academic future.  Furthermore, the results showed that introducing English at an early school stage will not negatively affect the students' first language, culture and identity. Instead it will promote them to evolve their personal and cultural skills and make them more open-minded and flexible when dealing with people of different cultures and countries.